Teacher Moonlighting and Absenteeism in South African Community Learning Centers: Implications for Teaching and Teacher Retention - Maceke, Ronnie Risimati; Mathebula, Nkarhi Excellent; Ntshangase, Mohammed; Nkalanga, Sibonangaye Dick (Humanis, 2026)
Community Learning Centres (CLCs), which are the main features of the Adult Education and Training system, offer necessary second-chance learning opportunities for out-of school youth, and adults who have never been to school or have dropped out early. Educator absenteeism, however, has, for a long time, been the major factor that has led to a decrease in public trust in such centres and, consequently, their effectiveness. The aim of the research was to explore the effect of teachers' moonlighting on absenteeism, teaching quality, and retention in South African CLCs. For this purpose, the study employed thematic analysis in line with Braun and Clarke's six (2021) step method to process secondary data obtained from previous research and institutional reports. This meticulous method of coding, gathering, and polishing themes made it possible to recognize the essential patterns of teacher behaviour and school issues. The research concluded that teachers take additional jobs just to meet the demands of their socio-economic lives. Educators' low salaries, their financial commitments, and the ever-rising demands of the household are a few of the factors that push teachers to find other jobs. Research findings show that moonlighting has a direct negative impact on teaching quality, as teachers have less time to prepare their lessons, deliver them, and interact meaningfully with students.